Non-covalent interactions between lignin and cellulase: From molecular mechanisms to precision regulation - Chengcheng Ye; Yuchen Han; Yanyi Tao; Lin Lv; Yu Long; Jianfeng Wu; Yongcan Jin; Wenjuan Wu (Bioresource Technology, 2026)

Multi-media antibiotics, intracellular and extracellular antibiotic resistance genes in marine protected areas of the South China Sea: Spatiotemporal distribution and multi-factor drivers of dissemination - Chengcheng Bu; Limin Ma; Yu Hua; Shaopeng Xu; Yutong Zhang; Huadong Yi; Yuchen Han; Haoyu Zeng; Yongzhi Wang; Xiaoying Xu; Qihui Zhao; Ruolan Jia; et al. (Marine Pollution Bulletin, 2026)

Chirality-engineered nanozymes orchestrate gut microbiota-host metabolism to shield against cardiotoxicity during cancer chemotherapy via the gut-heart axis - Xiaowan Fan; Shuyu Wang; Yuchen Wang; Shuai Han; Xiaoxi Chen; Yingting Huang; Shanzi Qin; Chengcheng Luo; Ying Wang; Xiyun Yan; Kelong Fan; Shipeng Ning (Science Bulletin, 2026)

Water–salt dual-control discrete element analysis of coupling mechanism between salt swelling and frost heave in sulfate saline soil - Chengcheng Luo; Yupeng Shen; Liwei Tan; Yv Sun; Yunxi Han (Computers and Geotechnics, 2026)

A daily-weekly-resolved δ18O record derived from a modern giant clam shell in the northern South China Sea: Implications for paleoclimate and paleoweather reconstruction - Chengcheng Liu; Nanyu Zhao; Guozhen Wang; Fan Luo; Shan Liu; Qiuju Yang; Murong Qi; Tao Han; Gang Xue; Miaohong He; Qiuli Li; Guoqiang Tang; et al. (Chemical Geology, 2026)

Systematic evaluation reveals the dynamics and functions of horizontal gene transfer widespread in algae - Limin Jia; Liangwei Li; Qijin Ge; Yanchun You; Kai Han; Sibo Wang; Jianwei Chen; Dazhi Wang; Xin Liu; Yunyun Zhuang; Guangyi Fan; Chengcheng Shi (Marine Life Science & Technology, 2026)

Biocontrol for Shrimp Disease: Comprehensive Review and a Bacterial Disease Biocontrol Practice - Xinyi He; Jian He; Minghong Liu; Menghuang Xu; Jianjun Jiang; Minze Liao; Chengcheng Wu; Peiyun Han; Long Zhang; Shaoping Weng; Zhixun Guo; Jianguo He (Reviews in Aquaculture, 2026)
Biocontrol is a key strategy for disease control, as it is environmentally friendly and widely applicable. This review elaborates on biocontrol in aquaculture, particularly in shrimp culture. Biocontrol in shrimp culture mainly relies on four strategies: (i) direct kill pathogen by Bdellovibrio or bacteriophages; (ii) suppression of intestinal pathogens with probiotics; (iii) reduction of environmental pathogens via probiotics, biofloc, or bivalves and fish; and (iv) blocking transmission of pathogens using predatory fish. “Shrimp‐fish polyculture” system for diseased biocontrol, which is convenient, effective, and affordable, focuses on blocking disease transmission routes. The efficacy of this strategy has been firmly established for white spot syndrome virus (WSSV). However, its application to other shrimp diseases is not widespread. Herein, a “shrimp‐fish polyculture” biocontrol plan was designed and successfully validated against Vibrio harveyi in shrimp. These findings successfully expand the application of the “shrimp‐fish polyculture” system to the control of bacterial diseases in shrimp, thereby offering new perspectives and methods for the biocontrol of diseases caused by various shrimp pathogens.

Astronomically Constrained Palaeoclimate Reconstruction and Drivers of Organic Carbon Burial: Evidence from the Lower Eocene Wenchang Formation, Eastern Yangjiang Sag - Rui Han; Shangfeng Zhang; Xinwei Qiu; Yaning Wang; Gaoyang Gong; Chengcheng Zhang (Journal of Marine Science and Engineering, 2026)
Sub-sag 21 in the eastern Yangjiang Sag, Pearl River Mouth Basin, South China, contains a thick lacustrine source-rock interval within the lower Wenchang Formation and is a major exploration target on the northern margin of the South China Sea. However, the timing of deposition during the early to middle Eocene remains poorly constrained, and the applicability of quantitative palaeoclimate reconstruction methods in low-latitude lacustrine basins requires further evaluation. In this study, we analyzed mudstones from the lower Wenchang Formation in Well E1. Using cyclostratigraphic constraints, we applied AstroGeoFit to construct an astronomically tuned age model, and combined palynological coexistence analysis with geochemical weathering proxies and linear–regression calibration to quantitatively reconstruct and cross-validate mean annual temperature and mean annual precipitation. Within this time-calibrated framework, we further quantified organic-carbon burial to evaluate the relationship between palaeoclimate evolution and organic-matter enrichment. The AstroGeoFit results indicate that the top of the lower Wenchang Formation in Well E1 is constrained to 44.563 Ma, and that the studied succession spans 50.249–44.563 Ma. Palynological coexistence analysis identifies three palaeoclimate phases within this interval. Method evaluation shows that the temperature reconstruction based on major-element geochemistry agrees well with the pollen-based temperature record, whereas one precipitation reconstruction based on weathering proxies shows the most robust agreement and stability relative to the pollen-based precipitation record. Reconstructed mean annual temperature ranges from 10.77 to 22.20 °C, and reconstructed mean annual precipitation ranges from 1188.27 to 1871.89 mm. Correlation analyses on the tuned timescale show that precipitation is more strongly associated than temperature with organic-matter accumulation parameters, including total organic carbon and organic carbon accumulation rate, indicating that organic carbon burial in the eastern Yangjiang Sag lake basin was mainly controlled by hydrological forcing. During the Early Eocene Climatic Optimum, carbon burial in low-latitude lakes was, therefore, not a simple response to elevated temperature, but instead reflected the integrated effects of precipitation, runoff, stratification, material supply, transport, and preservation. The evolutionary sequence further suggests that early high productivity was diluted by rapid sedimentation, reducing total organic carbon; subsequent cooling, lake deepening, and strengthened stratification enhanced organic matter preservation; and finally, tectonic subsidence together with regional humidification promoted the development and long-term preservation of high-quality lacustrine source rocks.

Multi-media distribution, source apportionment, and risk assessment of legacy and current-use organophosphorus pesticides in typical agricultural watersheds of China - Chengcheng Bu; Limin Ma; Weiwei Zhang; Yu Hua; Haoyu Zeng; Yuchen Han; Ruolan Jia; Qihui Zhao; Qi Wang; Yuefei Ruan; Chong Chen (Water Research, 2026)

Improving the thermostability, acid tolerance, and catalytic efficiency of Aspergillus terreus feruloyl esterase by rational design - Chengcheng Guo; Yaqin Wang; Funyi Menunge Kelly Joan; Zhiyu Liu; Hongxiang Han; Shenghua Wei; Ana Chen; Song Li (Food Bioscience, 2026)

Metal (oxyan) ion leaching and adsorption of phosphorous doped amorphous high-entropy hydroxide to spur water/seawater oxidation - Chengcheng Dong; Min Yao; Yunxia Kang; Han-Ming Zhang; Jinfeng Sun; Fang Zhao (Fuel, 2026)

A multi-task deep learning model based on transformer for simultaneously evaluating the TVB-N and TVC contents of chicken breasts using two different hyperspectral imaging - Xiaoxin Li; Mingrui Cai; Zhen Liu; Chengcheng Yin; Xinjie Tan; Jiangtao Wen; Yuxing Han (Food Chemistry, 2025)

Antibiotics, antibiotic resistance genes, and environmental drivers: Assessment of resistance pollution along the Yangtze River Basin - Chengcheng Bu; Chong Chen; Weiwei Zhang; Ru Zhang; Jinpeng Yu; Yu Hua; Haoyu Zeng; Yuchen Han; Ruolan Jia; Qihui Zhao; Yuefei Ruan; Limin Ma (Environmental Pollution, 2025)

Nano-traps intervening in liquid-liquid phase separation-mediated scavenging of cell-free DNA for macrophage polarization remodeling - Shuyuan Qu; Yilong Zhao; Yue Han; Xiaojie Zhou; Yueqi Ni; Kun Tan; Xizhen Luo; Jing Zhang; Bin Gu; Jiaolong Wang; Chengcheng Yin; Qin Zhao; et al. (Chemical Engineering Journal, 2025)

Time-division multiplexed thermistor-triboelectric bimodal tactile sensor for material recognition - Zhi Cao; Chengcheng Han; Zhiwei Zhang; Tian Tang; Hanlin Zhou; Yuxuan Zhou; Zhiyi Wu (Chemical Engineering Journal, 2025)

Soil-air exchange of substituted chlorobenzenes and volatile PFAS at contaminated sites: Impact of environmental factors and development of a fugacity-based model - Weiwei Zhang; Limin Ma; Jinpeng Yu; Chengcheng Bu; Yongzhi Wang; Haoyu Zeng; Yuchen Han (Journal of Hazardous Materials, 2025)

Study on processability, hydration characteristics and solidification mechanism of hazardous elements of high-phosphorus solid waste paste backfill materials - Yandong Han; Lang Liu; Shishan Ruan; Mengbo Zhu; Bo Yu; Huisheng Qu; Chengcheng Shao; Tiantian Li (Journal of Environmental Chemical Engineering, 2025)

Z-scheme TiO2@CeO2 nanozyme/sonodynamic combination therapy for breast cancer by immunomodulation of tumor microenvironment - Renyu Liu; Wei Wang; Chengcheng Zhang; Liangfang Shen; Rongrong Zhou; A'meng Han; Di Jing; Zijian Zhang; Xianbo Wu; Liu Deng; You-Nian Liu; Xin Zhang (Chemical Engineering Journal, 2025)

Multiple behaviour recognition of free-range broilers in cross-domain scenarios using MCA-YOLOv5 - Yang Guo; Junshu Wang; Peng Lin; Chengcheng Yin; Yuxing Han (Biosystems Engineering, 2025)

Gonadotropin inhibitory hormone (GnIH) induces glucose metabolism disorders and ovarian dysfunction in ovarian white follicles of hens - Bingqian Shen; Dongyang Han; Yuanyuan Xin; Jiani Zhang; Changlin Xu; Xingxing Song; Xin Zhang; Chengcheng Liu; Jiang Li; Yixian Wei; Xiaoye Wang; Chuanhuo Hu; et al. (Theriogenology, 2025)

Acetamiprid in Rizhao green tea: Residue dynamics, degradation pathways, and ecological risks via integrated experimental and computational approaches - Changjian Li; Shujie Zhang; Chengcheng Han; Xiaolin Han; Jian Song; Jian Ju; Huimin Zhu (Journal of Hazardous Materials, 2025)

Environmental and metabolic influences on daily to hourly element/Cashell of Tridacna derasa cultured under elevated Ba2+ background concentration conditions - Haotian Yang; Hong Yan; Chengcheng Liu; Nanyu Zhao; Shan Liu; Pengchao Zhou; Guozhen Wang; Hanfeng Wen; Tao Han; Jun Li; Jialong Hao; Ruiying Li; et al. (Global and Planetary Change, 2025)

An occupational health assessment of dinotefuran exposure in greenhouse vegetable workers: Metabolomic profiling and toxicokinetic analysis - Jiamin Li; Hao Zhang; Ke Zhao; Chengcheng Han; Changjian Li; Lei Fang; Haiyong Jia; Yong Wang; Hanqiu Tang; Qingfeng Zhai; Peng Xue (Journal of Hazardous Materials, 2025)

CRISPR-Cas9 mediated construction of a food-grade pyrroloquinoline quinone high-yielding Acetobacter pasteurianus Ab3 strain - Chengcheng Han; Kai Xia; Jiawen Ma; Xinle Liang; Wenjie Wang (Food Bioscience, 2025)

Adaptation and challenges for giant clam species under marine heatwaves - Jun Geng; Hong Yan; Chengcheng Liu; Nanyu Zhao; Shan Liu; Tao Han; John Dodson; Hanfeng Wen (Global and Planetary Change, 2025)

Electrochemically enhanced micro-electrolytic ceramic substrate infiltration system as an efficient approach for treatment of imidacloprid wastewater - Ru Zhang; Weiwei Zhang; Chengcheng Bu; Guangyao Chen; Shuyun Li; Yuchen Han; Haibin Ma; Anyong Xu; Desheng Wang; Limin Ma (Environmental Monitoring and Assessment, 2025)

Research on the activity of dry-discharge coal-fired slag of different particle sizes and their performance as precursors of alkali-activated backfilling cementitious materials - Yandong Han; Lang Liu; Shishan Ruan; Chengcheng Shao; Mengbo Zhu; Huisheng Qu (Environmental Research, 2025)

New factors driving in-plane uneven degradation of Pt in proton exchange membrane fuel cells at high current density - Kai Han; Xiaolong Li; Rongrong Zhang; Yongzhen Wang; Chao Li; Min Fan; Chengcheng Huang; Hongmei Liu; Zipeng Zhao; Zhaojing Ni (Chemical Engineering Journal, 2025)

Compatibility of modified magnesium slag-based backfill materials to polycarboxylate superplasticizer: Flow, water-film thickness and strength - Chengcheng Shao; Lang Liu; Xiaoyan Zhang; Lei Xie; Shishan Ruan; Yandong Han; Xiang Ding (Environmental Research, 2025)

Effects of temperature, relative humidity and soil organic carbon content on soil-air partitioning coefficients of volatile PFAS - Weiwei Zhang; Limin Ma; Songsong Chen; Chong Chen; Chengcheng Bu; Jinpeng Yu; Ru Zhang; Yongzhi Wang; Haoyu Zeng; Yuchen Han (Science of The Total Environment, 2024)

Prediction of nonlinear mechanical characteristics for metallic strip flexible pipe with bend stiffener constraints - Weidong Ruan; Kai Liu; Chengcheng Zhou; Xiangxi Han; Xiaofeng Gao; Kefu Qi (Ocean Engineering, 2024)

Differential characteristics of chemical composition, fermentation metabolites and antioxidant effects of polysaccharides from Eurotium Cristatum and Fu-brick tea - Zhengwei Tan; Pinglian Yu; Haoyan Zhu; Jiaobei Gao; Ning Han; Chengcheng Yang; Zhuo Shen; Chang Gao; Xingbin Yang (Food Chemistry, 2024)

Rational design and dynamic reconstruction of phosphorus-doped amorphous high-entropy oxysulfide for efficient overall alkaline water splitting - Han-Ming Zhang; Jiakang Li; Chengcheng Dong; Caizhen Zhu; Jian Xu; Lihao Zuo; Jinfeng Sun (Chemical Engineering Journal, 2024)

A time window averaging method to mitigate the impact of shell growth trends on Tridacna δ18O records - Tao Han; Hanfeng Wen; Nanyu Zhao; Chengcheng Liu; Guozhen Wang; Zhe Wang; Hong Yan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Application of Nanozymes and its Progress in the Treatment of Ischemic Stroke - Qing Han; Chengcheng Wang; Jian Liu; Cai Wang; Hongming Zhang; Qingbin Ni; Jingyi Sun; Ying Wang; Baoliang Sun (Translational Stroke Research, 2024)

An efficient transformer network for detecting multi-scale chicken in complex free-range farming environments via improved RT-DETR - Xiaoxin Li; Mingrui Cai; Xinjie Tan; Chengcheng Yin; Weihao Chen; Zhen Liu; Jiangtao Wen; Yuxing Han (Computers and Electronics in Agriculture, 2024)

Galla Turcica alleviates gingiva inflammation and alveolar bone resorption via regulating Th1/Th17 in a mouse model of periodontitis - Yakun Han; Chengcheng Yu; Yan Yu (Advances in Traditional Medicine, 2024)

Seasonal to interannual variations of daily growth rate of a Tridacna shell from Palau Island, western Pacific, and paleoclimatic implications - Hanfeng Wen; Hong Yan; Chengcheng Liu; Nanyu Zhao; Shan Liu; John Dodson; Tao Han; Jun Geng; Pengchao Zhou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Three-dimensional triboelectric nanogenerator manufacturing using water transfer printing - Shuangxing Cai; Chengcheng Han; Zhi Cao; Yongyang Chen; Jie Cao; Yuanyu Wang; Zhiyi Wu (Chemical Engineering Journal, 2024)

Quantitative reconstruction of a single super rainstorm using daily resolved δ18O of land snail shells - Guozhen Wang; Jibao Dong; Tao Han; Chengcheng Liu; Fan Luo; Haotian Yang; Miaohong He; Guoqiang Tang; Nanyu Zhao; Qian Zhang; Gang Xue; John Dodson; et al. (Science Bulletin, 2024)

Rainstorm erosion difference and topographical changes induced by heavy rainfall between afforestation and grassland restoration catchments on the Chinese Loess Plateau - Mingkui Hao; Zhao Jin; Da Luo; Guofan Cao; Chengcheng Jiang; Hao Han; Siqi Yang; Jing Zhang (Geomorphology, 2024)

SY-Track: A tracking tool for measuring chicken flock activity level - Xinjie Tan; Chengcheng Yin; Xiaoxin Li; Mingrui Cai; Weihao Chen; Zhen Liu; Junshu Wang; Yuxing Han (Computers and Electronics in Agriculture, 2024)

Reconstruction of ENSO variability using the standardized growth index of a Tridacna shell from Yongshu Reef, South China Sea - Jun Geng; Hong Yan; Chengcheng Liu; Tao Han; Shan Liu; Nanyu Zhao; Hanfeng Wen; Haotian Yang; Pengchao Zhou; Guozhen Wang; John Dodson (Science of The Total Environment, 2024)

Tetracycline inhibits the nitrogen fixation ability of soybean (Glycine max (L.) Merr.) nodules in black soil by altering the root and rhizosphere bacterial communities - Shuo Zhang; Wei Han; Tianqi Liu; Chengcheng Feng; Qun Jiang; Bo Zhang; Yukun Chen; Ying Zhang (Science of The Total Environment, 2024)

Constructing carbon-based materials loaded with MOFs to realize efficient anaerobic digestion of rural organic waste - Xiaomei Ye; Zhaoyan Jia; Yang Liu; Chengcheng Wang; Chunhui Cao; Yingpeng Zhang; Ting Han; Li Wang; Ting Guo; Yonglan Xi (Fuel, 2024)

Abnormal Brain Protein Abundance and Cross-tissue mRNA Expression in Amyotrophic Lateral Sclerosis - Yanni Ma; Tingting Jia; Fengqin Qin; Yongji He; Feng Han; Chengcheng Zhang (Molecular Neurobiology, 2024)
Due to the limitations of the present risk genes in understanding the etiology of amyotrophic lateral sclerosis (ALS), it is necessary to find additional causative genes utilizing novel approaches. In this study, we conducted a two-stage proteome-wide association study (PWAS) using ALS genome-wide association study (GWAS) data ( N = 152,268) and two distinct human brain protein quantitative trait loci (pQTL) datasets (ROSMAP N = 376 and Banner N = 152) to identify ALS risk genes and prioritized candidate genes with Mendelian randomization (MR) and Bayesian colocalization analysis. Next, we verified the aberrant expression of risk genes in multiple tissues, including lower motor neurons, skeletal muscle, and whole blood. Six ALS risk genes ( SCFD1 , SARM1 , TMEM175 , BCS1L , WIPI2 , and DHRS11 ) were found during the PWAS discovery phase, and SARM1 and BCS1L were confirmed during the validation phase. The following MR ( p = 2.10 × 10 −7 ) and Bayesian colocalization analysis (ROSMAP PP4 = 0.999, Banner PP4 = 0.999) confirmed the causal association between SARM1 and ALS. Further differential expression analysis revealed that SARM1 was markedly downregulated in lower motor neurons ( p = 7.64 × 10 −3 ), skeletal muscle ( p = 9.34 × 10 −3 ), and whole blood ( p = 1.94 × 10 −3 ). Our findings identified some promising protein candidates for future investigation as therapeutic targets. The dysregulation of SARM1 in multiple tissues provides a new way to explain ALS pathology.

Trajectory prediction of seagoing ships in dynamic traffic scenes via a gated spatio-temporal graph aggregation network - Xiliang Zhang; Jin Liu; Peizhu Gong; Chengcheng Chen; Bing Han; Zhongdai Wu (Ocean Engineering, 2023)

A novel method for solidification/stabilization of MSWI fly ash by graphene nanoplatelets synergistic alkali-activated technology - Tianru Li; Baomin Wang; Xiong Zhang; Xiao Han; Yunqing Xing; Chengcheng Fan; Ze Liu (Journal of Environmental Chemical Engineering, 2023)

Transcriptome analysis of Akebia quinata (Thunb.) Decne. and discovery of key enzyme genes in the phenylpropanoid biosynthesis pathway - Chengcheng Qian; Yatian Yang; Rui Wu; Bangxing Han; Deling Wu; Jinmei Ou (Acta Physiologiae Plantarum, 2023)

Effects of benthic bioturbation on anammox in nitrogen removal at the sediment-water interface in eutrophic surface waters - Jie Gao; Yue Zhi; Yuyue Huang; Sijie Shi; Qiujun Tan; Chengcheng Wang; Le Han; Jingmei Yao (Water Research, 2023)

Effect of nano silica on solidification/stabilization of heavy metal in alkali-activated MSWI fly ash solidified body - Tianru Li; Baomin Wang; Xiong Zhang; Xiao Han; Yunqing Xing; Chengcheng Fan; Ze Liu (Process Safety and Environmental Protection, 2023)

Spatiotemporal Dynamics of the Molecular Expression Pattern and Intercellular Interactions in the Glial Scar Response to Spinal Cord Injury - Leilei Gong; Yun Gu; Xiaoxiao Han; Chengcheng Luan; Chang Liu; Xinghui Wang; Yufeng Sun; Mengru Zheng; Mengya Fang; Shuhai Yang; Lai Xu; Hualin Sun; et al. (Neuroscience Bulletin, 2023)
Nerve regeneration in adult mammalian spinal cord is poor because of the lack of intrinsic regeneration of neurons and extrinsic factors – the glial scar is triggered by injury and inhibits or promotes regeneration. Recent technological advances in spatial transcriptomics (ST) provide a unique opportunity to decipher most genes systematically throughout scar formation, which remains poorly understood. Here, we first constructed the tissue-wide gene expression patterns of mouse spinal cords over the course of scar formation using ST after spinal cord injury from 32 samples. Locally, we profiled gene expression gradients from the leading edge to the core of the scar areas to further understand the scar microenvironment, such as neurotransmitter disorders, activation of the pro-inflammatory response, neurotoxic saturated lipids, angiogenesis, obstructed axon extension, and extracellular structure re-organization. In addition, we described 21 cell transcriptional states during scar formation and delineated the origins, functional diversity, and possible trajectories of subpopulations of fibroblasts, glia, and immune cells. Specifically, we found some regulators in special cell types, such as Thbs1 and Col1a2 in macrophages, CD36 and Postn in fibroblasts, Plxnb2 and Nxpe3 in microglia, Clu in astrocytes, and CD74 in oligodendrocytes. Furthermore, salvianolic acid B, a blood–brain barrier permeation and CD36 inhibitor, was administered after surgery and found to remedy fibrosis. Subsequently, we described the extent of the scar boundary and profiled the bidirectional ligand-receptor interactions at the neighboring cluster boundary, contributing to maintain scar architecture during gliosis and fibrosis, and found that GPR37L1_PSAP, and GPR37_PSAP were the most significant gene-pairs among microglia, fibroblasts, and astrocytes. Last, we quantified the fraction of scar-resident cells and proposed four possible phases of scar formation: macrophage infiltration, proliferation and differentiation of scar-resident cells, scar emergence, and scar stationary. Together, these profiles delineated the spatial heterogeneity of the scar, confirmed the previous concepts about scar architecture, provided some new clues for scar formation, and served as a valuable resource for the treatment of central nervous system injury.

Symbiont-screener: A reference-free tool to separate host sequences from symbionts for error-prone long reads - Mengyang Xu; Lidong Guo; Yanwei Qi; Chengcheng Shi; Xiaochuan Liu; Jianwei Chen; Jinglin Han; Li Deng; Xin Liu; Guangyi Fan (Frontiers in Marine Science, 2023)
Metagenomic sequencing facilitates large-scale constitutional analysis and functional characterization of complex microbial communities without cultivation. Recent advances in long-read sequencing techniques utilize long-range information to simplify repeat-aware metagenomic assembly puzzles and complex genome binning tasks. However, it remains methodologically challenging to remove host-derived DNA sequences from the microbial community at the read resolution due to high sequencing error rates and the absence of reference genomes. We here present Symbiont-Screener ( https://github.com/BGI-Qingdao/Symbiont-Screener ), a reference-free approach to identifying high-confidence host’s long reads from symbionts and contaminants and overcoming the low sequencing accuracy according to a trio-based screening model. The remaining host’s sequences are then automatically grouped by unsupervised clustering. When applied to both simulated and real long-read datasets, it maintains higher precision and recall rates of identifying the host’s raw reads compared to other tools and hence promises the high-quality reconstruction of the host genome and associated metagenomes. Furthermore, we leveraged both PacBio HiFi and nanopore long reads to separate the host’s sequences on a real host-microbe system, an algal-bacterial sample, and retrieved an obvious improvement of host assembly in terms of assembly contiguity, completeness, and purity. More importantly, the residual symbiotic microbiomes illustrate improved genomic profiling and assemblies after the screening, which elucidates a solid basis of data for downstream bioinformatic analyses, thus providing a novel perspective on symbiotic research.

Changes in the physicochemical, structural and emulsifying properties of chicken myofibrillar protein via microfluidization - Keying Han; Xiao Feng; Yuling Yang; Xiaozhi Tang; Chengcheng Gao (Innovative Food Science & Emerging Technologies, 2023)

Middle-Late Miocene paleoenvironmental evolution and its implications for hominoid distribution in the southeastern Tibetan Plateau - Wenxia Han; Chengcheng Ye; Shuang Lü; Tao Zhang; Xiaomin Fang; Weilin Zhang; Yibo Yang; Maodu Yan (CATENA, 2023)

Changes in Distribution Patterns for Larimichthys polyactis in Response to Multiple Pressures in the Bohai Sea Over the Past Four Decades - Qingpeng Han; Xiujuan Shan; Xianshi Jin; Harry Gorfine; Yunlong Chen; Chengcheng Su (Frontiers in Marine Science, 2022)
Understanding patterns of change in the distribution of species among their critical habitats is important for analyzing population dynamics and adaptive responses to environmental shifts. We investigated spatio-temporal changes in small yellow croaker ( Larimichthys polyactis ) using eight alternative models fitted to data from bottom trawl surveys conducted in the Bohai Sea each spring (spawning period) and summer during 1982–2018. These models included different combinations of local sea temperature, fishing pressure, and individual climate index (i.e., North Pacific index, NPI, and West Pacific index, WPI) as explanatory variables. Selection of the most parsimonious model for each season was based on Akaike’s Information Criterion (AIC). The model with NPI as its only explanatory variable was used as a base case for pre-analysis. In spring, a spatio-temporal model with sea temperature as a quadratic effect, plus the spatially varying effects of a climate index and fishing pressure was selected, as the AIC value of this model was reduced by 41.491 compared to the base case model without these effects. In the summer after spawning, the spatio-temporal model with WPI as a climate index covariate lagged by 1-year best explained the spatio-temporal distribution patterns of the stock. The results suggested that small yellow croaker populations significantly decreased in biomass in the Bohai Sea over the study period. A statistically significant northeastward shift in the center of gravity (COG) and a contraction in the distribution range occurred in summer throughout the study period ( p <0.05). During the spring sequence (1993–2018), a statistically significant northeastward shift in the COG was also found ( p <0.05). Our results showed that biomass-density hotspots of small yellow croaker in both seasons have shrunk or disappeared in recent years. Overall, these findings suggest that the spatio-temporal patterns of the populations in their spawning, feeding and nursery grounds have been influenced over the past 40 years by multiple pressures, and population density in the southwestern areas of the Bohai Sea declined faster and more drastically than in the northeastern areas. This study has important implications for developing targeted spatial conservation measures for small yellow croaker at various stages of its life history under different levels of stress.

Oxygen isotope temperature calibrations for modern Tridacna shells in western Pacific - Guozhen Wang; Hong Yan; Chengcheng Liu; Tao Han; Pengchao Zhou; Nanyu Zhao; Hanfeng Wen; Haobai Fei; John Dodson (Coral Reefs, 2022)

Data-Limited Stock Assessment for Fish Species Devoid of Catch Statistics: Case Studies for Pampus argenteus and Setipinna taty in the Bohai and Yellow Seas - Qingpeng Han; Xiujuan Shan; Xianshi Jin; Harry Gorfine; Tao Yang; Chengcheng Su (Frontiers in Marine Science, 2021)
For many fish stocks, such as Pampus argenteus and Setipinna taty in China, size composition data are more accessible than catch data. Varied results can arise when different length-based stock assessment models are applied to these data, and fishery managers often need to reconcile conflicting estimates of population status. Superensemble modeling, a relatively recent innovation in fish stock assessments commonly used in other fields, may provide an effective solution to resolving uncertainties among the results from multiple length-based models. To verify potential for this approach to improve estimates of population status, we applied ensemble modeling to fit simulated data of P. argenteus and S. taty in the Bohai and Yellow Seas using predictions from a length-based integrated mixed effects (LIME) and length-based spawning potential ratio (LB-SPR) models as covariables in a superensemble model developed in this study. All simulation modeling of P. argenteus and S. taty in the Bohai and Yellow Seas was conducted using the operating model in the R package LIME. Initially, the LIME and LB-SPR performances were tested separately under three scenarios of fishing mortality and recruitment variability (“equilibrium scenario,” “endogenous scenario,” and “one-way base scenario”). Then, estimates of spawning potential ratio (SPR) were combined with the superensemble models (a linear model, a support vector machines, a random forest and a boosted regression tree). We trained our superensemble models with 80% of the simulated data and tested them with the remaining 20%. Our results showed that superensemble modeling substantially improved the estimates of SPR, with support vector machines performing the best at estimating population status: precision improved by 12.7% for S. taty and 8% for P. argenteus on average (namely, median absolute proportional error decreased by 0.127 and 0.08 on average) compared to the individual models. This finding has important implications for fisheries management in the context of species for which catch data are unavailable. Applying the size composition survey data, the results from support vector machines superensemble model suggested that neither S. taty nor P. argenteus in the Bohai Sea in 2019 are overfished, but the stock status of P. argenteus warrants vigilant monitoring.

A 2-step algorithm combining glutamate dehydrogenase and nucleic acid amplification tests for the detection of Clostridioides difficile in stool specimens - Chengcheng Liu; Chenjie Tang; Yaping Han; Yuqiao Xu; Fang Ni; Ke Jin; Genyan Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Preparation of CuSe-PDA/g-C3N4 and its visible-light photocatalytic performance to dye degradation - Maojuan Bai; Chengcheng Xu; Xuanye Huang; Han Yin; Jun Wan (Environmental Science and Pollution Research, 2021)

Investigation of lipid profile in Acetobacter pasteurianus Ab3 against acetic acid stress during vinegar production - Chengcheng Han; Kai Xia; Jieqiong Yang; Hong Zhang; Matthew P. DeLisa; Xinle Liang (Extremophiles, 2020)

Design and Synthesis of Polymer Prodrugs for Improving Water-Solubility, Pharmacokinetic Behavior and Antitumor Efficacy of TXA9 - Yiwen Li; Chun Ye; Chengcheng Cai; Meng Zhao; Na Han; Zhihui Liu; Jianxiu Zhai; Jun Yin (Pharmaceutical Research, 2020)

Seminar on “Engineering and environmental geology in the permafrost region along the Sino-Russian-Mongolian Economic Corridor under the background of climate change” and the Annual Academic Conference of 2018 of ICL-CRLN and the Cold Region Landslide Research of IPL-WCoE held in Harbin - Ying Guo; Chengcheng Zhang; Qunli Han; Wei Shan (Landslides, 2019)

Significant genetic association of a functional TFPI variant with circulating fibrinogen levels and coronary artery disease - Duraid Hamid Naji; Chengcheng Tan; Fabin Han; Yuanyuan Zhao; Junhan Wang; Dan Wang; Jingjing Fa; Sisi Li; Shanshan Chen; Qiuyun Chen; Chengqi Xu; Qing K. Wang (Molecular Genetics and Genomics, 2018)

Cytoplasmic expression of a thermostable invertase from Thermotoga maritima in Lactococcus lactis - Han Bin Pek; Pei Yu Lim; Chengcheng Liu; Dong-Yup Lee; Xuezhi Bi; Fong Tian Wong; Dave Siak-Wei Ow (Biotechnology Letters, 2017)

The Roles of Tight Junctions and Claudin-1 in the Microbubble-Mediated Ultrasound-Induced Enhancement of Drug Concentrations in Rat Prostate - Yonggang Shang; Xiaoxiao Dong; Guangwei Han; Jia Li; Dong Cui; Chengcheng Liu; Longkun Li; Shanhong Yi (The Journal of Membrane Biology, 2015)

Mechanistic Aspects of the Photodynamic Inactivation of Vancomycin-Resistant Enterococci Mediated by 5-Aminolevulinic Acid and 5-Aminolevulinic Acid Methyl Ester - Chengcheng Liu; Yingli Zhou; Li Wang; Lei Han; Jin’e Lei; Hafiz Muhammad Ishaq; Jiru Xu (Current Microbiology, 2015)

High dose of extracellular ATP switched autophagy to apoptosis in anchorage-dependent and anchorage-independent hepatoma cells - Qing Wei; Ying Zhang; Lei Sun; Xiaoqing Jia; Wanwan Huai; Chengcheng Yu; Zhengkun Wan; Lihui Han (Purinergic Signalling, 2013)